The impact of a training curriculum for the rapid development of power and speed of the motor accuracy scoring football for youth ages (17-19 years old) - Ali, Muhsin (Journal of Physical Education, 2011)
This study aimed to prepare the training curriculum to develop strength characterized by speed, speed, kinetic score for young players to football in Iraq and determine the impact of the training program in the development of power characterized by the speed and Movement speed to score and I suppose the researcher training program affect significantly the results of post tests of the experimental group, which was applied as the curriculum and the number (10) players Reconstruction 17-18 and the other group is the control and the number (10) players Conclusions show that the training program had a positive impact in the outcome of the post tests of the experimental group